A Teaching Experience of the Human-Computer Interaction Course in a Master Program - Paz, Freddy Asrael (2019)
Learning-by-doing is an educational theory which establishes that the students learn in a more effective way if they are involved in experiences of the real world instead of passively listening. In the HCI course of the Master Program in Informatics, of the Pontifical Catholic University of Peru, the professors proposed the active-learning approach for the teaching of several topics related to HCI such as usability, user-centered design, human factors, accessibility, ergonomics and internationalization that are nowadays relevant concepts for the design process of graphical user interfaces. For this purpose, we received the committed collaboration of a local financial entity, the BBVA Continental Bank, which voluntarily agreed to establish a set of requirements for the design of GUIs that support the implementation of new features in ATMs. This proposed exercise has allowed the students to apply what they learned in real work situations, and to consolidate the discussed concepts from practice.